A Novel Soft Actuator for the Musculoskeletal System. Issue 5 (19th February 2018) - Wu, Lianjun; Chauhan, Indrajeet; Tadesse, Yonas
Abstract: The musculoskeletal system (MS) is essential for the movements of biological systems. Inspired by this natural structure, several attempts are made to create a synthetic MS. However, one of the challenges in developing an artificial MS for biomimetic robots is the lack of a high‐performance, low‐cost, light‐weight, and compact artificial muscle. In this Communication, a novel twisted and coiled artificial muscle is demonstrated, which is a promising actuator for the development of the artificial MS. The new muscle is made by twisting a nylon 6 fishing line precursor fiber and wrapping with a very thin (80 µm diameter) resistance wire. The resistance wire is not twisted during twist insertion of the polymer, which is very important for the performance of the muscle. The new muscle termed T C P N C F L is integrated in a 3D printed ball‐and‐socket‐based artificial MS. Characterization results show a remarkable tensile actuation (53% strain provided at 1.69 MPa for an input current of 0.22 A). Furthermore, a bioinspired design and fabrication of the synthetic MS is illustrated incorporating antagonistic pairs capable of reaching a bending angle of 20° within 1 s. These actuators can potentially be used in other soft robots, prosthetics, and orthotics advancing the progress in the area. Abstract : A new artificial muscle consisting of a very thin wire that is not twisted with the precursor fiber is demonstrated. A remarkable tensile actuation (53% strain under 1.69 MPa load for an input current of 0.22 A) and a bio‐inspired musculoskeletal system are demonstrated. The muscle can potentially be used in other soft robots, prosthetics, and orthotics.